The effects of maximising the UK’s tobacco control score on inequalities in smoking prevalence and premature coronary heart disease mortality: a modelling study - Kirk Allen (BMC Public Health, 2016)
Abstract Background Smoking is more than twice as common among the most disadvantaged socioeconomic groups in England compared to the most affluent and is a major contributor to health-related inequalities. The United Kingdom (UK) has comprehensive smoking policies in place: regular tax increases; public information campaigns; on-pack pictorial health warnings; advertising bans; cessation; and smoke-free areas. This is confirmed from its high Tobacco Control Scale (TCS) score, an expert-developed instrument for assessing the strength of tobacco control policies. However, room remains for improvement in tobacco control policies. Our aim was to evaluate the cumulative effect on smoking prevalence of improving all TCS components in England, stratified by socioeconomic circumstance. Methods Effect sizes and socioeconomic gradients for all six types of smoking policy in the UK setting were adapted from systematic reviews, or if not available, from primary studies. We used the IMPACT Policy Model to link predicted changes in smoking prevalence to changes in premature coronary heart disease (CHD) mortality for ages 35–74. Health outcomes with a time horizon of 2025 were stratified by quintiles of socioeconomic circumstance. Results The model estimated that improving all smoking policies to achieve a maximum score on the TCS might reduce smoking prevalence in England by 3 % (95 % Confidence Interval (CI): 1–4 %), from 20 to 17 % in absolute terms, or by 15 % in relative terms (95 % CI: 7–21 %). The most deprived quintile would benefit more, with absolute reductions from 31 to 25 %, or a 6 % reduction (95 % CI: 2–7 %). There would be some 3300 (95 % CI: 2200–4700) fewer premature CHD deaths between 2015–2025, a 2 % (95 % CI: 1.4–2.9 %) reduction. The most disadvantaged quintile would benefit more, reducing absolute inequality of CHD mortality by about 4 % (95 % CI: 3–9 %). Conclusions Further, feasible improvements in tobacco control policy could substantially improve population health, and reduce health-related inequalities in England.